Edukacja w perspektywie horyzontalnej = Education in the horizontal perspective - Gnitecki, Janusz (1945-2008) (Zielona Góra: Uniwersytet Zielonogórski)
Education in the horizon of a human activity is the main frame of this work. Forms and institutions of education, the aspects of life-long learning as well as education in practice are described in this paper.
Keywords: edukacja